Student Ride-Sharing System with Multi-Factor Authentication - Junaidih, Siti Nurhafiza; Abdullah, Zubaile (Applied Information Technology And Computer Science, 2024)
The Student Ride-Sharing System with Multi-Factor Authentication project aims to revolutionize transportation for Universiti Tun Hussein Onn (UTHM) students by addressing the challenges they face in arranging affordable and secure rides. In response to the existing manual ride-hailing system, which lacks proper verification measures and centralized control, this project introduces a secure online platform designed exclusively for UTHM students. This system emphasizes security with multi-factor authentication that consist of strong password and email one-time password. It mitigates risks associated with unauthorized access, data breaches and fraud. This project uses Agile software development life cycle (SDLC) approach and hypertext preprocessor (PHP). By fusing improved security measures including one-time password for verification and input validation with a user-friendly approach, the project offers an inviting solution that prioritizes the needs and safety of UTHM students.